Il linguaggio di Joseph Ratzinger, papa Benedetto XVI - Benedetti, Amedeo (Rivista di studi politici internazionali, 2010)
The paper focuses on the language of Pope Benedict XVI. Joseph Ratzinger (Marktl am Inn, Germany, 1927), one of the most significative leaders in the world, makes copious use of witty remarks, proverbs, biblical expressions, maxims of popular lore, scholastic logics, professorial techniques, that have a persuasive effect on the audience. L'Auteur analyse le language du pape Benoît XVI. Joseph Ratzinger (Marktl am Inn, Allemagne, 1927), un des chefs les plus significatifs dans le monde utilise fréquemment des descriptions subtiles, des proverbs, des expressions bibliques, des maximes de sagesse populaire, des logiques scolastiques, des techniques professorales pour obtenir un effet persuasif sur le public. PAROLE CHIAVE: Papa; Joseph Ratzinger; Benedetto XVI; Chiesa cattolica; Comunicazione politica